KARAKTERISTIK PERTUMBUHAN DAN WAKTU GENERASI ISOLAT Azotobacter sp. DAN BAKTERI ENDOFITIK ASAL EKOSISTEM LAHAN SAWAH - Mieke Rochimi Setiawati; Pujawati Suryatmana; Diyan Herdiyantoro; Zahra Ilmiyati (Jurnal Agroekoteknologi, 2014)
Azotobacter sp. and N2-fixation endophytic bacteria are microbes that play a role in fixation the N2 from the free air and helps supply of N to plants and can make efficient use of N derived from inorganic fertilizer. N2-fixation microbes utilization in rice fields can reduce the cost of production of rice plants. By studying the characteristics of the two types of beneficial bacteria that is expected to be engineered to enhance the role of these bacteria contribute in supplying N to rice crops. The method used in this study is exploratory and observe the characteristics of growth and generation time of bacteria for 72 hours. The results of this study indicate that the bacterial isolates of Azotobacter sp-1 has the highest population in 48 hours with a total population of 1.58 x107 cfu ml-1 , whereas bacteria Azotobacter sp-2 has the highest population in 60 hours with a total population of 3.12 x106 cfu ml-1 . Both N2-fixation endophytic bacteria populations reached the highest peak in the 60th hour with a total population of N2-fixation endophytic bacteria-1 at 1.12 x 108 cfu ml-1 of N2-fixation endophytic bacteria-2 of 9.4 x 107 cfu ml-1 of both isolates endophytic bacteria showed a similar growth pattern. Azotobacter sp. isolates from rhizosfir of the rice plant have a difference generation time, while the two isolates of N2-fixation endophytic bacteria from tissue of rice plants having the same generation time. Isolates of Azotobacter sp.-1 had the fastest of generation time, capable of generating new cells every 158.66 minutes or every 2.64 hours.